A new small molecule with indolone chromophore as the electron accepting unit for efficient organic solar cells. (February 2015) - Fan, Ling; Cui, Ruili; Jiang, Lihui; Zou, Yingping; Li, Yongfang; Qian, Dong
Abstract: A new small molecule (TIBDT) with indolone chromophore as the electron acceptor unit and benzodithiophene as electron donor unit was synthesized and first applied in organic solar cells (OSCs). TIBDT was characterized by NMR, TGA, UV–Vis absorption spectroscopy and cyclic voltammetry measurements. Results show that TIBDT possesses excellent thermal stability, appropriate absorption spectra, low-lying highest occupied molecular orbital (HOMO) level and high hole mobility. The OSCs based on TIBDT: PC71 BM (1:1, w / w ) showed a power conversion efficiency (PCE) up to 3.94% with an open circuit voltage ( V oc ) of 0.89 V, short circuit current ( J sc ) of 7.36 mA cm −2, fill factor (FF) of 60.2% under the illumination of AM 1.5 G, 100 mW cm −2 without solvent additives and thermal annealing treatment. These preliminary investigations show that indolone chromophore can probably be an excellent electron accepting unit for constructing high performance optoelectronic materials. Graphical abstract: Highlights: A small molecule (TIBDT) with indolone chromophore as electron acceptor unit was synthesized. TIBDT was well characterized and first applied in organic solar cells (OSCs). TIBDT demonstrates a power conversion efficiency of 3.94% with high V oc up to 0.89 V and FF of 0.60.